GaAs WET and Siconi Cleaning Sequences for an Efficient Oxide Removal. (1st January 2019) - Raynal, P. E.; Rebaud, M.; Loup, V.; Vallier, L.; Roure, M. C.; Martin, M.; Barnes, J. P.; Besson, P.
Abstract : Before metal deposit or epitaxial regrowth steps, efficient surface preparations are mandatory in order to remove both contaminants (C,  F) and surface oxides. In this paper, we assess several cleaning sequences and compare their efficiency toward GaAs oxides removal. As III/V materials are very reactive in the air, in-situ surface preparation schemes (conducted for instance in a Siconi chamber) might be useful on GaAs surfaces. This way, the queue-time issues associated with wet surface preparations could be avoided. In this study, GaAs substrates were chemically oxidized to first characterize the oxide removal efficiency of HF, HCl and Siconi processes. Then, a new surface preparation strategy was proposed based on i) a wet chemical treatment followed by ii) a standard Siconi process. In situ Parallel Angle Resolved X-ray Photoelectron Spectroscopy was used to study the chemical composition of the native or chemical oxides and evaluate the impact of the various treatments on the GaAs surface. SIMS analyses were used to measure/quantify the efficiency of surface preparations on Carbon and Arsenic / Gallium oxides removal.